Neoclassical Economics’ Immunisation Strategies Against Behavioural Economics: Popper’s Perspective - Aleksander Ostapiuk (Gospodarka Narodowa. The Polish Journal of Economics)
Although neoclassical economics faces frequent criticism, it remains the dominant paradigm, largely due to its immunisation strategies that rely on unfalsifiable concepts of utility and rationality. In this paper, I use Karl Popper’s philosophy to assess whether these strategies are justified. Firstly, I reconstruct Popper’s ideas on immunisation strategies, situational analysis, the rationality principle, and the metaphysical research programme. Next, I examine how neoclassical economics’ immunisation strategies counter critiques from behavioural economics. I conclude that neoclassical economics’ method does not produce empirical conjectures. I assess and evaluate this finding in relation to the “rationality principle”, as it parallels neoclassical economics’ optimisation axiom. Furthermore, I explore Popper’s relevance in the context of neoclassical economics’ recent incorporation of behavioural economics’ insights to show that my analysis is not purely historical.